The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.2188/jea.je20110026
|View full text |Cite
|
Sign up to set email alerts
|

Association of Sociodemographic Factors, Smoking-Related Beliefs, and Smoking Restrictions With Intention to Quit Smoking in Korean Adults: Findings From the ITC Korea Survey

Abstract: BackgroundFew studies have reported the factors associated with intention to quit smoking among Korean adult smokers. This study aimed to examine sociodemographic characteristics, smoking-related beliefs, and smoking-restriction variables associated with intention to quit smoking among Korean adult smokers.MethodsWe used data from the International Tobacco Control Korea Survey, which was conducted from November through December 2005 by using random-digit dialing and computer-assisted telephone interviewing of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
28
0
8

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 18 publications
13
28
0
8
Order By: Relevance
“…Females were less likely to smoke and smoked fewer cigarettes per day than their male counterparts and these findings are similar to those found in the general Korean population (Choi & Kim, 2008; Jung-Choi et al, 2012; Myung et al, 2012). In addition, females were more likely to be former smokers and to have previous quit attempts than their male counterparts.…”
Section: Discussionsupporting
confidence: 84%
“…Females were less likely to smoke and smoked fewer cigarettes per day than their male counterparts and these findings are similar to those found in the general Korean population (Choi & Kim, 2008; Jung-Choi et al, 2012; Myung et al, 2012). In addition, females were more likely to be former smokers and to have previous quit attempts than their male counterparts.…”
Section: Discussionsupporting
confidence: 84%
“…The finding in the current study is consistent with earlier studies conducted in other countries [44,54,55]. For instance, Driezen at al.…”
Section: Discussionsupporting
confidence: 94%
“…6,15 The current study also showed consistent findings, but unfortunately except the mosque none of the place showed strict restrictions. Most of the public places either allowed smoking everywhere or there was no rule.…”
Section: Discussionsupporting
confidence: 83%
“…6,15 Those who smoked a fewer number of cigarettes over their lifetime have been associated with increased abstinence rate. 6 The current study only included male smokers and did not show any influence of age on quitting intention or attempt but the light smokers significantly more likely to attempt quit or show intention to quit smoking.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation